Role of 3D Volumetric and Perfusion Imaging for Detecting Early Changes in Pancreatic Adenocarcinoma - Rahmanuddin, Syed; Korn, Ronald; Cridebring, Derek; Borazanci, Erkut; Brase, Jordyn; Boswell, William; Jamil, Asma; Cai, Wenli; Sabir, Aqsa; Motarjem, Pejman; Koay, Eugene; Mitra, Anirban; et al. (Frontiers in Oncology, 2021)
Purpose: There is a major lacking of the early detection method of Pancreatic cancer in high-risk groups therefore the main focus of this study is to find a solution in which TIDC (Time Intensity Density Curve) and 3D volumetric and perfusion imaging is used to prove that they can be the imaging biomarker with which the early detection of cancer in the pancreas will be possible. Experimental Designs: Quantitative retrospective and prospective study was done by analyzing multi-phase CT images of patients undergoing treatment of different stages of pancreatic adenocarcinoma using advanced 3d imaging software to identify the perfusion and radio density of tumor at different stages. Results: TIDC & Marley Equation proved useful in the quantification of tumor aggressiveness. Results show that perfusion and PDAC (Pancreatic Ductal Adenocarcinoma) displayed delays in the venous phase which is linked to VEGF (Vascular Endothelial Growth Factor)-related activity and exhibits the active and viable part of the tumor. 3d volume analysis of the patient's multi-phase CT scan showed clear changes in arterial and venous perfusion indicating the aggressive state of the tumor. Conclusion: TIDC and 3d volumetric analysis can play a significant role in defining the aggressiveness of early-stage tumor and response to therapy.